Developments in the characterisation of the catalytic triad of alpha-chymotrypsin: Effect of the protonation state of Asp102 on the 1H NMR signals of His57. - Bruylants, G; Redfield, C; Bartik, K (2007)
Protonated or not? 1H NMR spectra of α-chymotrypsin were recorded as a function of pH (from top to bottom pH 8.6, 5.1 and 4.2). Slow exchange is observed for the NH protons of His57 between two environments due to different protonation states of Asp102. © 2007 Wiley-VCH Verlag GmbH and Co. KGaA.